On the Nature of Capital - Veblen, Thorstein (Quarterly Journal of Economics, 1908)
The knowledge of ways and means is a communal product, 517.—Access to the common stock of technological knowledge is necessary to the production of a livelihood, 524.—With the advance of the industrial arts the possession of material equipment has become a requisite to the effective use of this common stock of knowledge and skill, 527.—Hence the great advantage of owning capital goods, 530; and hence the dominant position of the owner-employer in modern economic life, 535.—Summary conclusion, 541.